A case study of Major League Soccer : upcoming league expansion - Cocco, Adam R. (London : SAGE Publications: SAGE Business Cases Originals, 2018)
At the end of 2016, Major League Soccer (MLS) announced it will add four teams during the next five years. Two new expansion franchises will be granted in 2017, with another two announced in 2018. Based on increasing growth and demand, league executives believe this is the right time to expand to continue growing brand popularity and bring new media markets on board for upcoming media rights negotiations. In January 2017, 12 ownership groups applied for the next round of expansion. The ownership groups proposed teams in the following cities: Charlotte, NC; Nashville, TN; Indianapolis, IN; Detroit, MI; Phoenix, AZ; St. Louis, MO; Raleigh, NC; San Antonio, TX; Sacramento, CA; Cincinnati, OH; Tampa Bay, FL; and San Diego, CA. MLS will base its expansion decision on three key aspects: (a) an ownership group committed to spending resources for team-related developments; (b) strong local demographics and media markets; and (c) a comprehensive stadium plan for the long-term stability of the franchise. Each ownership group will fine-tune its case over the coming months. However, questions remain about which expansion groups present the strongest overall case for inclusion in the next wave of MLS expansion.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Major League Soccer (Organization); Soccer teams -- United States